Blowing in the wind: The infiltration of Sicilian Mafia in the wind power business - Valeria Virginia Checchi; Michele Polo (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2019)
Public policies in the last 20 years have promoted in Italy the investment in renewable energy sources within the framework of climate change policies. Investment in renewables received generous incentives, leading to a rapid expansion in the capacity installed. Judicial inquiries have uncovered several episodes of involvement of Mafia families in the rich wind power business in Sicily. We test whether such involvement can be confirmed looking at the overall investment in the region. Using data on wind farm installations at the municipality level we show that the probability of observing a wind farm in a municipality is higher if in the local territory there is a mafia family, whereas wind speed is (surprisingly) not significant. Plants of small size, that require a simplified procedure managed by the local administration, are the predominant pattern of investment. Hence the episodes unveiled by courts are paralleled by a wider correlation of mafia family entrenchment in a territory and wind farm investment. We compare this result with the case of Apulia, the other Southern region where there has been a large investment in wind farms, supported by an environmental friendly regional government and apparently immune from criminal infiltrations. Applying the same econometric model in the case of Apulia we find that wind speed matters whereas the presence of the local criminal organizations does not affect the probability of observing a wind farm.
Keywords: Q20; L94; K23; K32; K42; 330; mafia; wind farms; infiltration in legal businesses; Sicily